Solar street lamp device with fully automatic intelligent monitoring and control functions - ZHOU JUNMING (2018)
The invention discloses a solar street lamp device with fully automatic intelligent monitoring and control functions. The solar street lamp device comprises street lamp frames. The street lamp framesare fixedly mounted on the two sides of a road. Each street lamp frame is provided with a bracket sound-control street lamp device. The upper portion of each street lamp frame is provided with a roadsurface illuminating device and a solar power generating device, and the lower portion of each street lamp frame is provided with a storage battery device. The lower portion of the surface of the outer side of each street lamp frame is provided with a waterproof controller box. Each waterproof controller box is internally provided with a controller. The signal receiving end of each controller is electrically connected with a first light intensity sensor, a sound-control sensor and a second light intensity sensor. The power supply output end of each controller is electrically connected with anLED lamp and an LED illumin